WILLINGNESS TO ACCEPT AND SATISFACTION OF COVID-19 VACCINE IN EAST JAVA CULTURAL AREAS - Angga Erlando; Kemala Sari Agusti; Andre Pupung Darmawan; Hanif Amarullah (Indonesian Journal of Health Administration, 2023)
Background: Vaccinations are considered to be most effective solution to end a pandemic. Various issues develop inclusively regarding doubts about vaccines, which can be formed by various factors, such as social and cultural environment. Aims: This study aims to analyze factors that affect willingness to accept (WTA) COVID-19 vaccine in four dominant cultural areas in East Java (Arek, Madura, Mataraman and Pandalungan) and analyze what factors influence satisfaction of vaccination. Methods: This is quantitative research which analyzes 825 participants (40% men; 60% women). By using primary data the probit regression method is applied. We use dummy variables of WTA and level of satisfaction as dependent variables, while the independent variables include economic, health, socio-demographic and internal-external factors of vaccination program. Results: This research showed different results in each cultural area; WTA of vaccines was influenced by income, assets, employment, health, education, gender, and age, while satisfaction with vaccines is associated with side effects, type of vaccine, and time of service (AOR: 0.31 to 0.56, αlpha: 1%-10%). Conclusion: This study concludes that people of Arek and Mataraman tend to be willing and satisfied with vaccination, while Madura and Pandalungan show an opposite result due to lower accessibility, welfare, and culture. Keywords: COVID-19, East Java cultural areas, satisfaction, vaccine, willingness to accept